AN ANALYSIS OF ILLOCUTIONARY ACTS IN ALCOTT’S THE LITTLE WOMEN: A PRAGMATIC STUDY - Lalu, Nanda Yohana Gabriela; Wongkar, Yapi H.; Lolowang, Imelda S. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Language plays an important role in shaping character development in literary works, particularly in portraying women’s voices within specific social contexts. This study aims to analyze how illocutionary acts reflect the character development of the four March sisters Jo, Meg, Beth, and Amy in Louisa May Alcott’s The Little Women. This research employs a qualitative descriptive method with a pragmatic approach, focusing on speech act theory proposed by Searle. The data source of this study is the novel The Little Women, specifically the utterances produced by the four main female characters. Data were collected through documentation techniques, involving careful reading, identifying, and classifying utterances that contain illocutionary acts. The data were analyzed by categorizing the utterances into types of illocutionary acts and interpreting their functions in relation to character development and 19th-century social context. The findings reveal that each character demonstrates distinct dominant illocutionary acts that reflect her personality and personal growth. Jo frequently uses assertive and directive acts, indicating her independence and resistance to gender norms, while Meg’s speech shows internal conflict between desire and social expectations. Beth’s expressive acts reflect her gentle and selfless nature, whereas Amy’s assertive acts illustrate her ambition and maturity. These results show that illocutionary acts significantly contribute to character development in the novel. This study implies that speech act analysis can enhance literary interpretation and support the teaching of pragmatics through literary texts.